An inclusive study to elucidation the heavy metals-derived ecological risk nexus with antibiotic resistome functional shape of niche microbial community and their carbon substrate utilization ability in serpentine soil - Koner, Suprokash; Chen, Jung-Sheng; Hseu, Zeng-Yei; Chang, Ed-Haun; Chen, Kuang-Ying; Asif, Aslia; Hsu, Bing-Mu (Journal of environmental management, 2024)
Heavy metals (HMs) contained terrestrial ecosystems are often significantly display the antibiotic resistome in the pristine area due to increasing pressure from anthropogenic activity, is complex and emerging research interest. This study investigated that impact of chromium (Cr), nickel (Ni), cobalt (Co) concentrations in serpentine soil on the induction of antibiotic resistance genes and antimicrobial resistance within the native bacterial community as well as demonstrated their metabolic fingerprint. The full-length 16S-rRNA amplicon sequencing observed an increased abundance of Firmicutes, Actinobacteriota, and Acidobacteriota in serpentine soil. The microbial community in serpentine soil displayed varying preferences for different carbon sources, with some, such as carbohydrates and carboxylic acids, being consistently favored. Notably, 27 potential antibiotic resistance opportunistic bacterial genera have been identified in different serpentine soils. Among these, Lapillicoccus, Rubrobacter, Lacibacter, Chloroplast, Nitrospira, Rokubacteriales, Acinetobacter, Pseudomonas were significantly enriched in high and medium HMs concentrated serpentine soil samples. Functional profiling results illustrated that vancomycin resistance pathways were prevalent across all groups. Additionally, beta-lactamase, aminoglycoside, tetracycline, and vancomycin resistance involving specific bio-maker genes (ampC, penP, OXA, aacA, strB, hyg, aph, tet(A/B), otr(C), tet(M/O/Q), van(A/B/D), and vanJ) were the most abundant and enriched in the HMs-contaminated serpentine soil. Overall, this study highlighted that heavy-metal enriched serpentine soil is potential to support the proliferation of bacterial antibiotic resistance in native microbiome, and might able to spread antibiotic resistance to surrounding environment. [Display omitted] •Cr, Ni, Co ecotoxicity imbalance microbial C-source utilization in serpentine soil.•Vancomycin resistome induce within bacterial community of HMs rich serpentine soil.•HMs co-select the opportunistic bacteria functional adaptation in serpentine soil.•Opportunistic bacteria e.g. Lapillicoccus &Rubrobacter enriched in serpentine soil.•Key ARGs of native bacteria allied with β-lactamase, aminoglycoside, vancomycin.